The Taimyr fold belt, Arctic Siberia: timing of prefold remagnetisation and regional tectonics (Dataset) ... - Torsvik, Trond H; Andersen, Torgeir B (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: The Taimyr fold belt, Arctic Siberia: timing of prefold remagnetisation and regional tectonics ...